2011
DOI: 10.1007/978-3-642-22359-4_11
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning about Joint Action and Coalitional Ability in K n with Intersection

Abstract: Abstract. In this paper we point out that standard PDL-like logics with intersection are useful for reasoning about game structures. In particular, they can express coalitional ability operators known from coalition logic and ATL. An advantage of standard, normal, modal logics is a well understood theoretical foundation and the availability of tools for automated verification and reasoning. We study a minimal variant, multi-modal K with intersection of modalities, interpreted over models corresponding to game … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 16 publications
(29 reference statements)
1
15
0
Order By: Relevance
“…Research about the concept of shared actorship can be found in work on joint action and coalitions (e.g., Borgo [2007], Ågotnes and Alechina [2011], and Grossi et al [2007]). This line of investigation is relevant, as it looks into individual deliberation when coordination is required.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Research about the concept of shared actorship can be found in work on joint action and coalitions (e.g., Borgo [2007], Ågotnes and Alechina [2011], and Grossi et al [2007]). This line of investigation is relevant, as it looks into individual deliberation when coordination is required.…”
Section: Related Workmentioning
confidence: 99%
“…This amounts to finding all minimal coalition of agents who can achieve ϕ collectively[Ågotnes and Alechina 2011].…”
mentioning
confidence: 99%
“…However, these approaches only deal with the element of shared responsibility, neglecting the element of shared actorship. Research about the concept of shared actorship can be found in work on joint action and coalitions (e.g., [5,1,16]). This line of investigation is relevant as it looks into individual deliberation when coordination is required, whereas work on delegation (e.g., [11,25]) sheds light on how norms can be transferred among individuals and groups.…”
Section: Related Workmentioning
confidence: 99%
“…The paper is based on [19]; the main additional contribution of the current paper is the sharpening of the embedding result. In [19], we defined a translation from C L into joint action logic with a fixed number of actions.…”
Section: Introductionmentioning
confidence: 99%
“…In [19], we defined a translation from C L into joint action logic with a fixed number of actions. In the current paper, we define a translation from C L which "reads off" the required number of actions from the C L formula.…”
Section: Introductionmentioning
confidence: 99%